PERKEMBANGAN USAHA INDUSTRI KERAJINAN GERABAH, FAKTOR YANG MEMPENGARUHI ,DAN STRATEGI PEMBERDAYAANYA PADA MASYARAKAT DI DESA MELIKAN KECAMATAN WEDI KABUPATEN KLATEN - Hastuti, Indra (Universitas Muhammadiyah Surakarta, 2012)
This research aims to determine the development of the pottery industry enterprises, the factors that influence the development of the pottery industry business and to formulate appropriate empowerment to the community in the village of potterycraftsmen Melikan Wedi Klaten. Type District of research is a form of qualitative research with applied research , which took place in the village pottery handicraft industry center Melikan. The analysis in this research was done by using inductive analysis using a model of interactive analysis and preparation of community empowerment strategies with a SWOT analysis using cross strategy. The results showedbusinesses Melikan indusatri pottery village development. Factors affecting the development is the whole capital, human resources, technology, raw materials, natural disasters. Craftsmen organization, public policy, strategy formulation results in the formof community development planning, namely: (i) establishment of community conservationists pottery industry, (2) training in entrepreneurship and innovative potterymaking skills, (3) the development of capital and (4) drying equipment procurement.